A new heat supply strategy for CO2 capture process based on the heat recovery from turbine exhaust steam in a coal-fired power plant. (15th January 2022) - Guo, Liheng; Ding, Yudong; Liao, Qiang; Zhu, Xun; Wang, Hong
Abstract: A new heat supply strategy for the CO2 capture process based on the heat recovery from turbine exhaust steam was proposed and evaluated. A water-steam cycle, a CO2 capture unit, a CO2 compression unit, and an enhanced two-stage heat pump were simulated for a 600 MW coal-fired power plant using Aspen Plus. Effects of the working medium, the exhaust pressure of the turbine, and reboiler temperature on the heat pump efficiency were studied. The integrated configurations were simulated and the effects of reboiler duty, exhaust steam pressure, and reboiler temperature on the thermodynamic performance of the plant station were discussed. Results indicated that the utilization of internal heat exchangers improved effectively the coefficient of performance (COP) of the two-stage heat pump by 13.3–22.0%; the heat pump recovered effectively the latent heat of exhaust steam, and a lower CO2 desorption temperature would significantly contribute to a higher COP of the heat pump system and greater thermodynamic performance of the proposed integrated configuration with heat pump. A net electric efficiency penalty of 7.07% and a fuel utilization efficiency of 51.58% were obtained when the reboiler temperature was 90 °C. Highlights: A new heat supply strategy for CO2 capture was proposed. Heat recovered from turbine exhaust steam was used for CO2 desorption. The performance of the two-stage heat pump system was evaluated. The PCC-HP integrated configuration is suitable for a coal-fired power plant.